ANALISIS HUBUNGAN LATAR BELAKANG PENDIDIKAN KELUARGA DAN DAERAH ASAL MAHASISWA TERHADAP PEMILIHAN PROGRAM STUDI DI UNIVERSITAS HKBP NOMMENSEN MEDAN - Sinaga, Rani Farida; Simbolon, Lolyta Damora; Malau, Farmin; Situmorang, Mahanda Dinaria (MES: Journal of Mathematics Education and Science, 2023)
Universitas HKBP Nommensen consists of 11 faculties and 33 study programs for undergraduate and postgraduate levels. Students generally come from regencies / cities in North Sumatra province plus from several nearby provinces with different family education backgrounds. This study aims to analyze the relationship between family background and region of origin on the selection of study programs. This type of research is ex-post facto using a quantitative approach. The subjects in this study were students of Universitas HKBP Nommensen Medan. The research instrument used is a questionnaire. The data collected is analyzed based on statistical analysis. The results showed the magnitude of the influence of family educational background on the selection of study programs, it can be seen from the coefficient of determination (r2) of 0.254 which shows that family educational background has an influence on the selection of study programs by 25.4%. Based on the results of the analysis of the data collected, it can be concluded that there is a positive and significant influence of family education background but not with the area of origin of students on the selection of study programs.